ショウワ キチ ニオケル カンソク ロケット ケイカク ニホン ナンキョク チイキ カンソクタイ ノ ホウコク - 村山, 雅美; ムラヤマ, マサヨシ; 楠, 宏; クスノキ, コウ; 川口, 貞男; カワグチ, サダオ; MURAYAMA, Masayoshi; KUSUNOKI, Kou; KAWAGUCHI, Sadao (国立極地研究所, 1972)
P(論文) 昭和基地におけるロケット観測計画は日本学術会議南極特別委員会が勧告し,国立科学博物館極地研究センターが実施に協力し,最終的に南極地域観測統合推進本部によって決定される.昭和基地のロケット発射場に1969年1月に建物3棟を建設した(コントロールセンター,レーダーテレメーター室,組立調整室).観測ロケットとしてS-160(最高高度約90km)とS-210(約120km)の2種が選定された.1970年1月には発射台,ランチャー,レーダー設備などの設置を完了し,2月にはS-160JA1,S-160JA2の2機の飛しょうに成功した.この際電子密度およびオゾン密度の分布を高さ約90kmまで測定した.1971年,1972年における上記2種のロケットによる観測計画も付記した. The programme of the use of sounding rockets at Syowa Station in Antarctica was proposed by the National Antarctic Committee of the Science Council of Japan. The Polar Research Center, National Science Museum, has taken the responsibility for detailed planning, co-operated by other organizations concerned. The programme has been officially approved by the Promoting Headquarters of the Japanese Antarctic Research Expedition under the direction of the Minister of Education. The rocket range at Syowa Station was inaugurated in January 1969, erecting three buildings, namely, a control centre, a telemetry station, and a rocket assembly shop. Two kinds of rockets, S-160 (peak altitude about 90km) and S-210 (about 120km), were selected to be used in the initial stage of the research programme. In January 1970, a launcher was connected with the assembly shop and necessary equipment was installed for the first test launching of S-160. In February 1970, two test flights for measuring electron density and ozone concentration were successfully accomplished, reaching to an altitude of about 90 km. Future programme of launching six S-210 and one S-160 in the austral winter of 1971 and 1972 is described. departmental bulletin paper